Generalized Beltrami flows and other closed-form solutions of an unsteady viscoelastic fluid - F. Labropulu (International Journal of Mathematics and Mathematical Sciences)
We study flows of an unsteady non-Newtonian fluid by assuming the form of the vorticity a priori. The two forms that have been considered are ∇2ψ=F(t)ψ+G(t), which is known as the generalized Beltrami flow and ∇2ψ=f(t)ψ+g(t)y.